Cost Management Practice Techniques and Performance of Quoted Fast-Moving Consumer Goods Companies in Nigeria - Oyedeji, R. O.; Aribaba, F. O.; Ahmodu, A. O.; Ajao, K. O.; Shittu, S. A. (The Journal of Accounting and Management, 2023)
The purpose of this study was to examine the effect of cost management practice techniques on the performance of fast-moving consumer goods in Nigeria. The research method used for this study was an ex-post-facto research design with a population of 35 listed FMCG companies in Nigeria. Quantitative data were sought from the five (5) years of the annual published audited financial report of the selected companies between 2016 - 2020. Purposive sampling techniques were used to select Nigeria's top five traded FMCG companies. The statistical method used was descriptive, Generalized Linear Model (GLM) regression statistics and correlational analysis to test the research hypotheses. The statistical tool employed was econometrics view (E-view) software to analyse the data. The findings of the study revealed the coefficient estimates that budgetary control (r = 709680.4; p = 0.0228 < 0.05), activity-based costing (r = 825267.1; p = 0.0003 < 0.05) and standard costing (r = 4.079554; p = 0.0045 < 0.05) are statistically significant at 0.05 levels while the life-cycle costing (r = -6900.199; p = 0.9540 > 0.05) variable is negatively related but not statistically insignificant with the performance of FMCG in Nigeria. Thus, the correlational result depicts that only budgetary control and standard costing techniques are positively correlated, while activity-based costing and life-cycle costing are negatively correlated. Though only the life-cycle costing hypothesis was sustained, the other hypotheses were rejected. The study concluded that good costing techniques could be seen in identifying, measuring, and quantifying effective cost management practices on FMCG firm performance. Based on these conclusions, it was advised that additional research be done in other economic sectors to determine how cost management practices affect the performance of FMCG companies in Nigeria.